Implementation of Good University Governance: Top Management Support and State University Performance - Cahyana Agus; Tanjung Dahri; Khairi Inayah Syahwani Asty (E3S Web of Conferences, 2023)
The implementation of the process of achieving good university governance carried out at state universities in managing academic and nonacademic domains involves the support of top management and university performance. This study investigates the impact of the implementation of good university governance, top management support, and the performance of State Universities in Indonesia with data processing and analysis using PLS Structural Equation Modeling (SEM). The results of the study illustrate that the implementation of good university governance has a positive and significant effect on top management support, the implementation of good university governance has a positive and significant effect on university performance, and top management support has no effect on university performance. Efforts need to be increased on the dimensions of stakeholder participation, adequacy of resources (financial, infrastructure, information systems), and the internal processes of higher education.